Farm animal behavior : characteristics for assessment of health & welfare - Ekesbo, Ingvar (CABI, 2011)
Animal behaviour is the basis for ascertaining their welfare. This undergraduate-level textbook is organised into three sections covering all major farm animals of the world, both mainstream and specialist: large farm animal species (horses, cattle, swine, sheep and goats), poultry and farmed birds and non-domesticated animals such as deer